(3TQM GdThGgO GdUZQis - (3eMehO Hf CMeO Hf ehSi Hf CMeO, CHh eMeO, HOQ GdOjf GdYjfj GdMfaj,J (B855 (3g` s ((3Ydj Hf MSjf Hf Ydj Gdegfdj GdTGaYj s)
(3ChdgG (B:s
(3hHYO, jbhd(B: (3Ef LdI ef GdCPcjGA hNdI ef GdCdHGA hNGWHhG HCf TQM GdThGgO GdPj febJg s
(3BNQgG (B:s
(3hGdhghH eHGdZI hGgH, hGdeLRd ef CLRd EPG CYWi YWGA cKjQkG bGd GdeDda QMeg Gddg(B: (3hgPG BNQ eG GNJUQfGg ef GdThGgO s
(3cJHJ ef fSNI cJHJ ef fSNI GdeDdas
(3HChdgG Jedc SfI (B991(3g`s
(3hJedc BNQ TQGA ef ajV Gddg CafOj HGdBSJGfI SfI (B1197(3g`s
(3HgG fXGe GdJYbjHIs
(3HChdgG agQS s
(3bQf GdfSN (B:s
Keywords: (3GdfMhs